a) 1 - 5y = 3y
b) 5n-4=2n+1
c) 5x-1=-3x
Soluções para a tarefa
Respondido por
0
Resposta:
Explicação passo-a-passo:
) (+7x) + (-3x) = b) (-8x) + (+11x) =c) (-2y) + (-3y) = d) (-2m… ... b)3x. c)-5y. d)-3m. e)2a². f)0. g)2x. h)-5n. i)11x. j)6x. k)-5y. l)0. m)-7x ... 5/4m. 4 4 4. e) (+2/3x) – (–3/2x) = veja o SINAL (-)(-) = +. (+2/3x) + (3/2x).
Perguntas interessantes
Português,
8 meses atrás
Português,
8 meses atrás
História,
8 meses atrás
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Geografia,
1 ano atrás
Artes,
1 ano atrás